The Epidemic of Neonatal Abstinence Syndrome, Historical References of Its’ Origins, Assessment, and Management - Gomez-Pomar, Enrique; Finnegan, Loretta P. (Frontiers in Pediatrics, 2018)
Neonatal Abstinence Syndrome (NAS) refers to a constellation of signs that are present in some newborn infants resulting from the abrupt cessation of passive transfer of maternal opioids used during pregnancy. The classic NAS refers to infants born to mothers who used opioids during pregnancy, but the term has broadened to include infants whose mothers have used or abused other psychoactive substances during pregnancy that contribute to the expression of the syndrome. Pregnant women who use opioids do so illicitly, and/or as medically prescribed for pain relief, and/or as medication assisted treatment for opioid dependence. The first case of NAS in infants and the subsequent treatment (or lack thereof) was reported in 1875 and was called Congenital Morphinism. By 2012, the incidence of NAS increased to more than 30 per 1000 hospital live births, along with an increase in the number of infants being treated pharmacologically for NAS, resulting in an increase in the length of stay and healthcare expenses. We present historical references on NAS, the various factors and events that led to its increasing prevalence and today’s current epidemic. We also review the current tools to assess infants with NAS and treatment options in its management.